Descriptors to predict dye-sensitized semiconductor based photocatalyst for hydrogen evolution reaction - Sappati, Subrahmanyam; George, Leena; Swamy, Vincent Paul; Devi, R. Nandini; Ghosh, Prasenjit (ChemCatChem, 2019)
Discovering efficient photocatalysts for hydrogen production from water splitting is highly desirable. Computational studies can help in rational designing of such catalysts through high throughput screening of materials. However, for that purpose one needs to identify descriptors that not only connects material properties with their functionality but are easy and inexpensive to compute. Using a combination of density functional theory based calculations and experiments we show two descriptors, namely, charge injection efficiency and electron hole separation, that can be used for in silico design of new and efficient dye-sensitized-semiconductor composites as catalysts for hydrogen evolution reaction.
Keywords: charge injection; descriptor; dye-sensitized semiconductors; electron-hole separation; H-2 evolution